Late Cretaceous–early Paleocene ostracod biostratigraphy of Scientific Drilling Sk1(N) in the Songliao Basin, northeast China. (July 2014) - Qu, Haiying; Xi, Dangpeng; Li, Sha; Colin, Jean Paul; Huang, Qinghua; Wan, Xiaoqiao
Abstract : Cretaceous non-marine deposits are widespread in China and have been studied comprehensively. The Songliao Basin in northeast China is thought to be well suited for investigation of Cretaceous biostratigraphy. However, despite much research having been conducted in the basin, little is known about its Late Cretaceous biostratigraphy and paleoenvironment. Here, we establish a high-resolution biostratigraphy of the Late Cretaceous based on ostracods from borehole SK1(n) in the Songliao Basin, northeast China. As part of the present study, 45 species assigned to 20 genera have been recovered, with one new species ( Ilyocypris bisulcata n. sp.) and five ostracod assemblages: the Cypridea gunsulinensis – Mongolocypris magna assemblage, which is marked by the first occurrence (F.O.) of Ilyocyprimorpha with nodes and spines; the Ilyocyprimorpha – Limnocypridea sunliaonensis–Periacanthella assemblage, which ranges from the F.O. of Ilyocyprimorpha with nodes and spines to the F.O. of Strumosia sp.; the Strumosia inandita assemblage from the F.O. of Strumosia sp. to the lower occurrence (L.O.) of Strumosia inandita ; the Talicypridea amoena – Metacypris kaitunensis – Ziziphocypris simakovi assemblage from the F.O. of Mongolocypris apiculata (Cea) and Talicypridea amoena to the F.O. of Ilyocypris sp.; and the Ilyocypris assemblage from the F.O. of Ilyocypris sp. to the L.O. of Ilyocypris bisulcata n. sp. Moreover, the zonal fossil Ilyocypris bisulcata n. sp. of Zone 5 is here described for the first time from the upper Mingshui Formation, and Paleocene charophyte genera including Neochara and Grovesicahra have been found to coexist with the Zone 5 fauna. The age of the Ilyocypris Assemblage is assigned to the latest Maastrichtian to the earliest Danian.